PEMANFAATAN MINYAK OLI BEKAS SEBAGAI BAHAN BAKAR ALTERNATIF DENGAN PENCAMPURAN MINYAK PIROLISIS - Asman Darsono Asidu, Laode; Hasbi, Muhammad; Aksar, Prinob (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The purpose of this research is to produce physical characteristic data, including density and dynamicviscosity from mixing of used oil and pyrolysis oil, producing flame of mixing used oil and pyrolysis oil, andalso to produce efficient use of pressured stove kerosene And mixture of used oil and pyrolysis oils towardsthe use of gas fueled stoves. This research was conducted at University Halu Oleo Faculty of MechanicalEngineering Laboratory and Integrated Chemical Research Laboratory, math and science fakulty UniversityHalu Oleo. The results of this research indicated that the mass density and the viscosity of each percentageof used oil and pyrolysis oil mixture are increased, the rate of flow of spent kerosene oil and pyrolysis oil ateach percentage of mixture is sufficient. Decrease in Fuel Flow Rate, Characteristic The flame generated onmixing used oil and pyrolysis oils is red yellow with a maximum height of 25 cm at each percentage ofmixing, and The use of pressured stoves fuel and used oil mixtures and pyrolysis oils is more efficient againstthe use of gas-fired stoves , With a ratio of 4 liters of water.Keywords: Used Oil, Pyrolysis Oil, Pressure Gas, Pressure Cooker.